2022
DOI: 10.3389/fcell.2022.883841
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Secretion of Plant Extracellular Vesicles and Their Benefits to Human Health: A Mini Review

Abstract: Mechanisms devoted to the secretion of proteins via extracellular vesicles (EVs) have been found in mammals, yeasts, and plants. Since they transport a number of leader-less proteins to the plasma membrane or the extracellular space, EVs are considered part of Unconventional protein secretion (UPS) routes. UPS involving EVs are a relatively new field in plants. Aside from their role in plant physiology and immunity, plant extracts containing EVs have also been shown to be beneficial for human health. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…There are more macromolecules (such as cellulose and starch) in plant extracts, and the components are more complex, which renders the extraction of vesicles more difficult 69 , 70 . The combination of different isolation methods may extract nanovesicles with higher purity than a single method, and therefore the combined isolation method has been deeply explored and applied in recent years.…”
Section: Isolation and Stability Of Pnvsmentioning
confidence: 99%
“…There are more macromolecules (such as cellulose and starch) in plant extracts, and the components are more complex, which renders the extraction of vesicles more difficult 69 , 70 . The combination of different isolation methods may extract nanovesicles with higher purity than a single method, and therefore the combined isolation method has been deeply explored and applied in recent years.…”
Section: Isolation and Stability Of Pnvsmentioning
confidence: 99%
“…To date, several studies have revealed the existence of different routes involved in EV or AV biogenesis and their cellular release in plants; however, not all of them have been fully elucidated [ 6 , 16 , 20 , 26 , 30 ]. Among the known biogenesis pathways described in the literature, multivesicular body (MVB)–plasma membrane (PM) fusion is the most studied and well characterised ( Figure 2 A).…”
Section: Insights Into Plant Extracellular Vesicles Biogenesis and Re...mentioning
confidence: 99%
“…True EVs which are present in the extracellular milieu have been isolated from the following plant sources ( Figure 1 ): (i) apoplastic fluid [ 6 , 8 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], (ii) exudates [ 21 ], and (iii) conditioned culture media (CCM) [ 4 , 22 , 23 , 38 , 39 , 40 , 41 , 42 , 43 ]. Meanwhile, several recent reviews focus on the isolation and features of edible-plant-derived nanovesicles, outlining their promising biological properties [ 8 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other types of P-EVs include vesicles originating from vacuoles that the plants use to respond to environmental attacks. For example, the vacuolar content is released outside the cell membrane in vesicular form during pathogen infections, to counteract the dissemination of pathogens within the plant [16]. In Figure 1, a schematic representation of P-EVs biogenesis and release is reported.…”
Section: Introductionmentioning
confidence: 99%